Exploring Models of Care and the Perceived Impact in an Offender Rehabilitation Program - Carolan, Caoimhe (International journal of offender therapy and comparative criminology, 2022)
Offender rehabilitation programs incorporating positive psychology interventions such as a strengths-based model can be effective. This study explores the perceived model of service provided by an offender rehabilitation service and the perceived impact that this service has on the lives of its clients. A qualitative methodology was employed in the context of an action research design, using semi-structured interviews with key stakeholders. The data were analyzed using thematic analysis which is an independent and reliable approach to qualitative analysis. The findings suggest that participants perceive the organization to be operating a strengths-based approach and this is perceived as having the potential to have a range of positive effects for clients. Some contrasting views were also identified within the participant groups and these are discussed in this paper. The results of this study complement the existing research and have several implications for future research in this area.